Effects of Palm Vitamin E on Bone-Formation-Related Gene Expression in Nicotine-Treated Rats. (28th August 2012) - Abukhadir, Seham Salem Ahmed; Mohamed, Norazlina; Makpol, Suzana; Muhammad, Norliza
Abstract : The study determines the effects of palm vitamin E on the gene expression of bone-formation-related genes in nicotine-treated rats. Male rats were divided into three groups: normal saline olive oil (NSO), nicotine olive oil (NO), and nicotine palm vitamin E (NE). The treatment was carried out in 2 phases. During the first 2 months, the NSO group received normal saline while the NO and NE groups received nicotine 7 mg/kg, 6 days a week, intraperitoneally. The following 2 months, normal saline and nicotine administration was stopped and was replaced with oral supplementation of olive oil for the NSO and NO groups and oral supplementation of palm vitamin E (60 mg/kg) for the NE group. Both femurs were harvested to determine the gene expression of bone morphogenetic protein-2 (BMP-2), Osterix (OSX), and Runt-related transcription factor 2 (RUNX2). Nicotine significantly downregulated the gene expression. This effect was reversed by palm vitamin E treatment. In conclusion, palm vitamin E may play a role in osteoblast differentiation and can be considered as an anabolic agent to treat nicotine-induced osteoporosis.